Repeated Corrected Simpson’s 3/8 Quadrature Method for Solving Fredholm Linear Integral Equations of the Second Kind - Mansoor, Wafaa F.; Shraida, Shaymaa M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we use the repeated corrected Simpson’s 3/8 quadrature method for obtaining the numerical solutions of Fredholm linear integral equations of the second kind. This method is more accurately than the repeated corrected Trapezoidal method and the repeated Simpson’s 3/8 method. To illustrate the accuracy of this method, we give a numerical example